Patterns of Village Fund Corruption Prevention Based on Fatuleu Local Wisdom in Kupang Regency, Indonesia - Medan, Karolus Kopong; Kase, Dhesy Arisandielis; Bunga, Gerald Aldytia (Journal of Posthumanism, 2025)
This research-based article discusses the development of a corruption prevention model for village funds based on the local wisdom of the Fatuleu indigenous community in Kupang Regency, Indonesia.The study highlights the local wisdom within the Fatuleu indigenous community, which has strong potential to prevent the crime of village fund corruption. This socio-legal anthropological is used in this study. The data collection methods used include in-depth interviews, observations, and documentation.The study reports that the Fatuleu indigenous community perceives corruption as an unethical act akin to abakat/nabak (stealing another person's belongings). Specifically, such unethical actions include abakat loid/abakat none or nabak loid/nabak none (embezzlement of money), and akliut loid/akliut none or amoet loid/amoet none (financial fraud). The study also finds that the Fatuleu indigenous community possesses various forms of local wisdom that can serve as preventive measures against village fund corruption, particularly through the traditional rituals of lasi nekmese and lasi pisit.